Exotic Species Elicit Decoupled Responses in Functional Diversity Components of Freshwater Fish Assemblages in Chile - Castro-Morales, S (Elsevier B.V., 2021)
In the freshwater basins of central Chile, 28 exotic species have been introduced, which have contributed to increase taxonomic diversity. Nevertheless, how these species have modified the components of functional diversity in these assemblages, a key aspect in learning about their present and future stability within an ecosystem, is unknown. In this study, we analyzed how the introduction of exotic species affects the functional diversity components of richness (FRic), divergence (FDiv), specialization (FSpe), and functional originality (FOri). Additionally, we simulated the effect of the loss (extinction/extirpation) of threatened native species. To do so, we gathered information on the distribution and functional characters of native and exotic species. Through Principal Coordinates Analysis (PCo), we obtained three independent axes (PCoA1, PCoA2, and PCoA3), which allowed us to define a multidimensional space and then to calculate FRic, FDiv, FSpe, and FOri. Our results indicate that richness and functional originality have increased significantly with the introduction of exotic species (263% and 32%, respectively). In contrast, functional divergence and specialization have remained the same. The possible extinction of threatened native species may promote increases in functional originality, decreases in functional richness and divergence, and unchanged functional specialization. On the other hand, a subset of exotic species presents novel features, while another shows redundant features with native ichthyofauna. We emphasize that the possible extinction of native species currently classified as threatened may lead to the disappearance of unique functional groups, which puts at risk the persistence and stability of these assemblages. © 2021